PREPARATION OF FUTURE TEACHERS BEFORE COMMUNICATION - L.V. Kondrashova (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the significance of pedagogical intercourse as an important component o f future teachers' professional and pedagogical training.